Are women inferior to men as teachers ... according to students? - Binderkrantz, Anne Skorkjær (Politica, 2019)
International studies have found a gender difference in student evaluations where female teachers are evaluated lower than their male colleagues. This article investigates whether this is also the case in the Danish context. The article draws on evaluations from Aarhus BSS where a common procedure is in place for evaluating all teaching across study programs with varying gender composition of students and teachers. The material includes almost 30,000 student evaluations of more than 1,000 different teachers. Rather than a general gender bias, the analysis finds a relation between the composition of teachers, student gender and the evaluation of teachers of different gender.